The population dynamics of Spodoptera frugiperda after its invasion in Lampung Province, Indonesia - Lestari, Puji; Swibawa, I Gede; Fitriana, Yuyun; Suharjo, Radix; Utomo, Setyo Dwi; Hartaman, Maman (Universitas Lampung, 2024)
Spodoptera frugiperda is an invasive pest that attacks maize throughout Indonesia. As an invasive pest, the population of S. frugiperda continues to increase exponentially, leading to outbreaks. Both internal factors (biology) and external factors (weather, host, and natural enemies) can affect the growth rate of pest populations. This research was conducted to assess the population dynamics of S. frugiperda based on the extent of its infestation and damage to maize post-invasion in Lampung Province. Observations were made in maize fields in 15 districts of Lampung Province from 2019 to 2022. Damage intensity was calculated based on the leaf damage scale. Weather data from 2019 to 2022 was obtained from the Lampung Province Central Statistics Agency. The research results indicate that upon the initial introduction of S. frugiperda to Lampung Province, the population increased exponentially, as observed based on the level of infestation and damage to maize. There was an outbreak from late 2019 to early 2020, and after that, there was a population decline. The population increase coincided with the early rainy season, which is associated with the beginning of the maize planting season. Although the level of damage to the maize is considered slight, S. frugiperda can cause anywhere between 21.94% to 51.38% of damage.